Bioavailability of butorphanol after intranasal administration to horses - Ferreira, V. (2020)
The aim of the present study was to describe butorphanol pharmacokinetics and bioavailability following intranasal administration to horses. Six adult horses received 0.05 mg/kg butorphanol, in a randomised crossover design, by either intravenous or intranasal route. Plasma concentrations of bu-torphanol were measured at predetermined time points using liquid chromatography/mass spectrome-try assay. After intravenous injection, mean ±SD butorphanol steady-state volume of distribution and clearance was 3.20 ± 1.77 L/kg and 3.18 ± 1.47 L/kg/h, respectively. Terminal half-lives for butor-phanol after intravenous and intranasal administrations were 0.68 ± 0.17 h and 1.79 ± 1.43 h. For intranasal administration, absorption half-life and peak plasma concentration were 0.43 ± 0.33 h and 1.95 ± 1.7 ng/mL, respectively. Bioavailability was 54.45 ± 20.09%. Intranasal butorphanol administration in horses is practical, not stressful and well tolerated. Therefore, it might be a substitute to the intravenous route in adult horses.